Desain Dan Pembangunan Sistem Layanan Virtual Penjualan Berbasis Website di PT. Adidaya Andalan Asia - Anjelita Septiurma Gea; Ricky Ramadhan Harahap; Rahmadani (CV. Hawari, 2026)
The development of information technology has encouraged companies to shift from manual sales processes to more effective and efficient computerized systems. This study aims to design and develop a web-based virtual sales service system at PT Adidaya Andalan Asia that integrates centralized management of product data, customer data, sales transactions, and sales reporting. The system was developed using the PHP programming language and a MySQL database with a modular system architecture that is easy to expand. System testing was conducted functionally using the black-box method, including alpha testing by developers and beta testing by users, to ensure that the system operates according to requirements. The results show that the web-based virtual sales service system improves sales process efficiency, minimizes data recording errors, and provides accurate and easily accessible sales information to support evaluation and managerial decision-making at PT Adidaya Andalan Asia.